(3fgL GdeSJQTOjf aj CUhd GdOjfs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3dNUJ ajg eHGOF GdbhGYO GdcdGejI hQDhS GdeWGdH GdCUhdjI faY Gddg Hg WdGH Gdjbjf Efg NjQ ehab heYjf ELGHI dSDhGd GdhGdO GdYRjR eMeO Cjg Gddg JYGdi HYfGjJg hhabg ddNjQ (B...s
(3BNQgG (B:s
.. (3hGdaSb dZI GdNQhL Yf GdTjA hGdaCQI ahjSbI dNQhLgG ef HjJgG haj GdTQY GdNQhL Yf WGYI Gddg JYGdi (B... (3hdjcf BNQ eG fhQOg aj gPg GdebOeI hef CQGO GdJWhjd aYdjg HcJGHfG efJgi GdhUhd hGdefGgL hZjQgG ef cJHGfG JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/ 227s
(3GdPQjYI (B24 \ 257 ( 2222)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds